Immunogenicity of Recombinant Lipid-Based Nanoparticle Vaccines: Danger Signal vs. Helping Hand - Temchura, Vladimir; Wagner, Jannik; Damm, Dominik (Pharmaceutics, 2024)
Infectious diseases are a predominant problem in human health. While the incidence of many pathogenic infections is controlled by vaccines, some pathogens still pose a challenging task for vaccine researchers. In order to face these challenges, the field of vaccine development has changed tremendously over the last few years. For non-replicating recombinant antigens, novel vaccine delivery systems that attempt to increase the immunogenicity by mimicking structural properties of pathogens are already approved for clinical applications. Lipid-based nanoparticles (LbNPs) of different natures are vesicles made of lipid layers with aqueous cavities, which may carry antigens and other biomolecules either displayed on the surface or encapsulated in the cavity. However, the efficacy profile of recombinant LbNP vaccines is not as high as that of live-attenuated ones. This review gives a compendious picture of two approaches that affect the immunogenicity of recombinant LbNP vaccines: (i) the incorporation of immunostimulatory agents and (ii) the utilization of pre-existing or promiscuous cellular immunity, which might be beneficial for the development of tailored prophylactic and therapeutic LbNP vaccine candidates.
CRIS-Team Scopus Importer:2024-02-02
Keywords: adjuvants; cellular immunity; heterologous T cell help; immunogenicity; intrastructural help; lipid-based nanoparticles; liposomes; Toll-like receptor ligand; universal T cell epitope; vaccine antigen